Natural convection from a Plane Vertical Porous Surface in Non Isothermal - Saha, S. C. (Nonlinear Analysis: Modelling and Control, 2004)
In this paper, laminar natural convection flow from a permeable and isothermal vertical surface placed in non-isothermal surroundings is considered. Introducing appropriate transformations into the boundary layer equations governing the flow derives non-similar boundary layer equations. Results of both the analytical and numerical solutions are then presented in the form of skin-friction and Nusselt number. Numerical solutions of the transformed non-similar boundary layer equations are obtained by three distinct solution methods, (i) the perturbation solutions for small ξ (ii) the asymptotic solution for large ξ (iii) the implicit finite difference method for all ξ where ξ is the transpiration parameter. Perturbation solutions for small and large values of ξ are compared with the finite difference solutions for different values of pertinent parameters, namely, the Prandtl number Pr, and the ambient temperature gradient n.
Keywords: porous surface; non-isothermal surroundings; body force